Estrus response and fertility rate in Kundhi buffaloes following estrus synchronization in breeding season (Journal of Advanced Veterinary and Animal Research, 2015)
The aim of the present study was to compare theeffect of two estrus synchronization treatments i.e.,Ovsynch alone and Ovsynch plus Controlled InternalDrug Release (CIDR), on the occurrence of estrus andconception rate in Kundhi buffalo during breedingseason in Pakistan. Forty Kundhi buffaloes wererandomly selected and were divided into threegroups; Group A (n=16; Ovsynch) received 2 mLGnRH intramuscularly (i/m) on day 0 and 9. On day 7,5 mL prostaglandin F2? (PGF2? analogue) wasadministered through i/m route. The buffaloes ofGroup B (n=17; Ovsynch+CIDR) received 2 mLGnRH on day 0 along with implantation of CIDR. Onday 7, the CIDR was removed, and 5 mL PGF2?analogue was injected through i/m route. A seconddose of GnRH was administered through i/m routeafter 48 h of PGF2? inj. in both groups. Group C (n=7;control) received 2 mL normal saline through i/mroute on day 0, 7 and 9. The buffaloes of all threegroups were artificially inseminated twice (12 h and24 h after the second GnRH inj.) using frozen-thawedsemen. Estrus response differed significantly (P